Malocclusion, psycho-social impacts and treatment need: A cross-sectional study of Tanzanian primary school-children - Mtaya Matilda; Astrom Anne N; Brudvik Pongsri (BMC, 2008)
Abstract Background studies on the relationship between children's malocclusion and its psycho-social impacts are so far largely unexplored in low-income countries. This study aimed to assess the prevalence of malocclusion, reported dental problems and dissatisfaction with dental appearance among primary school children in Tanzania. The relationship of dissatisfaction with socio-demographic characteristics, clinically defined malocclusion and psychosocial impacts of dental anomalies was investigated. Orthodontic treatment need was estimated using an integrated socio-dental approach. Method One thousand six hundred and one children (mean age 13 yr) attending primary schools in the districts of Kinondoni and Temeke completed face to face interviews and a full mouth clinical examination. The survey instrument was designed to measure a Kiswahili translated and culturally adapted Child Oral Impact on Daily Performance (Child-OIDP) frequency score, reported dental problems, dissatisfaction with dental appearance/function and socio-demographic characteristics. Results The prevalence of malocclusion varied from 0.9% (deep bite) to 22.5% (midline shift) with a total of 63.8% having at least one type of anomaly. Moderate proportions of children admitted dental problems; ranging from 7% (space position) to 20% (pain). The odds ratio of having problems with teeth position, spaces, pain and swallowing if having any malocclusion were, respectively 6.7, 3.9, 1.4 and 6.8. A total of 23.3% children were dissatisfied with dental appearance/function. Children dissatisfied with their dental appearance were less likely to be Temeke residents (OR = 0.5) and having parents of higher education (OR = 0.6) and more likely to reporting problem with teeth position (OR = 4.3) and having oral impacts (OR = 2.7). The socio-dental treatment need of 12% was five times lower than the normative need assessment of 63.8%. Conclusion Compared to the high prevalence of malocclusion, psycho social impacts and dissatisfaction with appearance/function was not frequent among Tanzanian schoolchildren. Subjects with malocclusion reported problems most frequently and malocclusion together with other psycho-social impact scores determined children's satisfaction with teeth appearance- and function.